Peningkatan Pelayanan PAUD melalui Pelatihan Pertolongan Pertama pada Bayi dan Anak Sakit Kepada Guru PAUD di Wilayah Blitar - Ning Arti Wulandari; Zaenal Fanani; Bisepta Prayogi (STIKes Patria Husada Blitar, 2015)
first aid treatment is given to the person who got the accident or sudden pain that comes before getting help from medical personnel (Haryanto, 2013). The culture of women working in the public sphere encourages moms to find a replacement for his role in a while to nurture and educate her child for Working Moms (Ariani, 2013). Infant and preschool child had an accident prone (Short and Gray, 2009). Some of the things that encourages authors to perform community services through first aid training in infants and the sick children to early childhood education Teachers. The partners in this activity was PGTK Yaa Bunayya Kalipang Lodoyo;10 people and all of the early childhood education teacher ABA 2 add up to 17 people. The method of this activity was to do a pre test, applications training through lectures and demonstrations continued with the post test and evaluation skills. After it was done an evaluation of the satisfaction of caregivers against first aid on sick children conducted by the teacher. The results were of 80 71% caregivers said satisfied with the first aid on babies and sick children, 71% of teachers have a good skill in providing first aid on babies and sick children. Based on statistical tests with Wilcoxone signed rank test p = 0.000 showed any change of teacher knowledge about first aid on babies and sick children. Therefore, health and education should be create a newprogram in providing health services especially in early childhood education level.